Gel network comprising UV crosslinked PLGA-b-PEG-MA nanoparticles for ibuprofen topical delivery. (21st October 2019) - Eroglu, Ipek; Gultekinoglu, Merve; Bayram, Cem; Erikci, Acelya; Ciftci, Samiye Yabanoglu; Ayse Aksoy, Eda; Ulubayram, Kezban
Abstract: Ibuprofen is a non-steroidal anti-inflammatory drug for the treatment of Rheumatoid Arthritis and osteoarthritis. In this study, we prepared topical gel network for enhancement of ibuprofen penetration, maintenance of controlled release and increased patient compliance. Nanoparticles containing ibuprofen were prepared by means of emulsion formation/solvent diffusion method using synthesized copolymer. Nanoparticles were then conjugated with aminoethylmethacrylate, resulting in ibuprofen-loaded nanoparticles in PLGA- b -PEG-MA structure. Ibuprofen-loaded gel networks were developed by crosslinking nanoparticles via UV exposure. Suitability for topical application has been assessed through characterization of particle size, zeta potential, morphology, encapsulation efficiency, in vitro release, cytotoxicity and enhancement of in vitro wound healing. The mean diameter of nanoparticles was measured as 230 ± 20 nm. Gel network formulations with higher particle size (2800 ± 350 nm) and zeta potential (39.8 ± 9.2 mV), depending on conjugation of methacrylate within copolymeric structure, and having encapsulation efficacy of 73.6 ± 2.8% were prepared. The in vitro release of ibuprofen was sustained for more than 7 hours. Gel network improved collagen synthesis, type I collagen mRNA expression and fibrosis in dose dependent manner. Based on this, we can conclude that PLGA- b -PEG gel network might be a promising systems for the local delivery of ibuprofen in RA patients.